Inherent electrochemistry and activation of chemically modified graphenes for electrochemical applications - Moo, James Guo Sheng (2013)
Graphene research is currently at the frontier of electrochemistry. Many different graphene-based materials are employed by electrochemists as electrodes in sensing and in energy-storage devices. Because the methods for their preparation are inherently different, graphene materials are expected to exhibit different electrochemical behaviors depending on the functionalities and density of defects present. Electrochemical treatment of these “chemically modified graphenes” (CMGs) represents an easy approach to alter surface functionalities and consequently tune the electrochemical performance. Herein, we report a preliminary electrochemical characterization of four common chemically modified graphenes, namely: graphene oxide, graphite oxide, chemically reduced graphene oxide, and thermally reduced graphene oxide. These CMGs were compared with graphite as a reference material. Cyclic voltammetry was used to ascertain the chemical functionalities present and to understand the potential ranges in which the materials were electroactive. Electrochemical treatment with either an oxidative or a reductive fixed potential were then carried out to activate these chemically modified graphenes. The effects of such electrochemical treatments on their electrocatalytic properties were then investigated by cyclic voltammetry in the presence of well-known redox probes, such as [Fe(CN)6]4−/3−, Fe3+/2+, [Ru(NH3)6]2+/3+, and ascorbic acid. Thermally reduced graphene oxide exhibited the best electrochemical behavior amongst all of the CMGs, with the fastest rate of heterogeneous electron transfer (HET) and the lowest overpotentials. These findings will have far-reaching consequences for the evaluation of different CMGs as electrode materials in electrochemical devices.